If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(c + -8 + -3) + -3(2c + 12) = -84 Reorder the terms: 5(-8 + -3 + c) + -3(2c + 12) = -84 Combine like terms: -8 + -3 = -11 5(-11 + c) + -3(2c + 12) = -84 (-11 * 5 + c * 5) + -3(2c + 12) = -84 (-55 + 5c) + -3(2c + 12) = -84 Reorder the terms: -55 + 5c + -3(12 + 2c) = -84 -55 + 5c + (12 * -3 + 2c * -3) = -84 -55 + 5c + (-36 + -6c) = -84 Reorder the terms: -55 + -36 + 5c + -6c = -84 Combine like terms: -55 + -36 = -91 -91 + 5c + -6c = -84 Combine like terms: 5c + -6c = -1c -91 + -1c = -84 Solving -91 + -1c = -84 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '91' to each side of the equation. -91 + 91 + -1c = -84 + 91 Combine like terms: -91 + 91 = 0 0 + -1c = -84 + 91 -1c = -84 + 91 Combine like terms: -84 + 91 = 7 -1c = 7 Divide each side by '-1'. c = -7 Simplifying c = -7
| 2x+x+2=5x-10 | | .05x+.10(200-x)=.45x | | 0.09w=1.8 | | (a+4)(a+5)=0 | | -132=-39 | | -(c+10)+3(2c-6)= | | -132=39 | | -3v-v=16 | | -9b=-117 | | 35x+9=55 | | -n+2n=4 | | -8b=-117 | | -7x-3=4 | | 6n-7=2n+17 | | 11x-4x^2-344= | | 1/3(s-2)=s+4 | | (x+9)(x+9)=18 | | 344=11x-4x^2 | | 3(2z-1)=6z+5 | | -28=-7(1-8b)-5(4b-3) | | (x-2)(x+3)=24 | | 32x+1=3+6 | | 2x+1+6x=81 | | -6n+9=1-8n | | -17b=-2.21 | | -17=-2.21 | | 7x-3=2x-12 | | y=-4+3x | | -34e=-3.74 | | 5x+1-7=-1 | | 25+37-2x=11 | | y=-3x+(-4) |